Brand Experience, Brand Equity and Customer Satisfaction in Samsung Smartphone Users: An Islamic Business Ethics Perspective - Fadhillah, Fadhillah; Kurniawan, Muhammad; Selvina, Mia (Journal of Economics and Social Sciences (JESS), 2025)
Technology is something that we cannot avoid in this life because technological progress will run in accordance with scientific progress. Every innovation is created to provide positive benefits to human life, provide a lot of convenience, as well as a new way of doing human activities. Indonesia is dominated by the Samsung smartphone brand. Based on a survey conducted by the American Customer satisfaction Index (ACSI) in 2023, the Samsung Customer Satisfaction Index experienced instability in several market segments that there were complaints from customers about the quality of Samsung smartphone products. The purpose of this study is to look at the influence of brand experience and brand equity on customer satisfaction of Samsung smartphone users in the perspective of Islamic Business Ethics. The research method uses quantitative explanatory, with a sample of 100 respondents processed using the help of SmartPls 4 software, and the results show Brand experience and Brand equity have a significant positive effect on Customer satisfaction Samsung smartphones, Customer satisfaction on Samsung smartphone products is a natural thing and is allowed in Islam as long as it is not used for things that contain elements of crime, do not harm others and do not cause damage to economic activities (QS. Ash-Shu'ara: 183).